(untitled) (Proceedings of International Conference on BioScience and Biotechnology, 2017)
Traditional herbal medicines (THM’s) are still being used worldwide in at least 80% of the population, mainly in developing countries, due to the assumption that they are safer and cheaper. However, these medicines are now being adulterated with synthetic drugs causing toxic effects. One such drug is Sibutramine, a drug used for weight loss. Although Sibutramine has several promising weight loss effects, it causes several toxic side effects; this resulted in its banning and withdrawal from the market. Despite this, it is still being adulterated in herbal medicines and needs to be detected. It is detected using several analytical techniques such as TLC, GC, LC-MS, LCMS/MS, QTOF-LC/MS and more recently, spectroscopic techniques. Out of all the techniques, QTOF-LC/MS detected concentrations of Sibutramine adulterated in 9.4 mg (not clear what this means) and had LOD and LOQ values of 0.4- 2.0 µg kg-1 and 1.3- 6.0 µg kg-1 respectively; therefore, QTOF-LC/MS is the best technique developed up to date when compared to all the other techniques. However, research is currently ongoing to combine spectroscopic techniques other than MS, to overcome disadvantages such as lack of global information, false-positive results, time and labor consumption to detect Sibutramine adulteration in the future.